Microsurgical repair of a Terminal Myelocystocele: 2D operative video - Formentin, Cleiton (2022)
An 8-month-old boy was referred to our department with a protruding soft mass in the lumbosacral region since birth, with intact overlying skin. The patient had clubfoot, and congenital scoliosis. On neurological examination, he had preserved muscle strength, but evolved with distal weakness and increasing in the lumbar mass volume. MRI confirmed the diagnosis of terminal myelocystocele by the typical finding of a trumpet-like flaring meningocele. Terminal myelocystocele classically presents as a large lumbosacral mass with skin cover, containing fat, cerebrospinal fluid, and neural tissue1,2. The spinal cord herniates through the dysraphic spine and terminates at a neural placode, whereas the central canal opens into a CSF-filled, ependyma-lined cavity3. We present a 2D operative video comprising microsurgical repair of the defect, resection of the nonfunctional caudal cyst wall, reconstruction of the proximal neural placode, and duroplasty. Received: 21 February 2022. Accepted: 19 April 2022. Published: 15 May 2022.